Employee’s satisfaction on using e-siar portal among management department at Ibu Pejabat Polis Kontinjen Negeri Sembilan / Rasyidah Shaffie - Shaffie, Rasyidah (Faculty of Business and Management, 2013)
e-Siar Portal plays an important role in every staffs in Ibu Pejabat Polis Kontinjen Negeri Sembilan. Therefore, this paper are aim to investigate the employee's satisfaction on using e-Siar portal among Management Department at Ibu Pejabat Polis Kontinjen Negeri Sembilan. Based on previous study, shows that the information quality, system quality, service quality give impact to the employee's satisfaction. The measurement is use by the framework is adapted from the Delone McLean framework in Portal Effectiveness. This research is used questionnaires that were distributed to 150 staffs of Management Department at the Ibu Pejabat Polis Kontinjen Negeri Sembilan. The questionnaires are adopted from the previous journal. Thus, data were collected and analyzed by using SPSS version 18.0 to interpret the finding of this study. The findings indicated the level of employee's satisfactions on using e Siar portal at Ibu Pejabat Polis Kontinjen Negeri Sembilan.